Domestic Violence Reporting in Konde.co Media through Fiqh Perspective: Critical Discourse Analysis - Farokhah, Fiqih Aisyatul (KARSA Journal of Social and Islamic Culture, 2024)
This article aims to examine the portrayal of women in Konde.co media, the language utilized by the media to shape perceptions of gender roles, and the Islamic fiqh perspective on cases of domestic violence experienced by women, as depicted in mass media campaigns that perpetuate harmful gender stereotypes and normalize violence against women. The issue of domestic violence, particularly when viewed through an Islamic lens, remains a topic of significant interest to the public. It is crucial to analyze domestic violence cases from a fiqh standpoint, considering how Islamic jurisprudence plays a crucial role in dispelling misconceptions about gender disparities in the context of domestic violence. Fiqh also serves as a mechanism for societal regulation, intersecting with mass media influences. By employing Norman Fairclough's critical discourse analysis, this study highlights the impact of mass media, such as Konde.co, on shaping public perceptions of domestic violence. The findings suggest that Konde.co perpetuates gender ideologies, as evident in the content of news articles and the platform's name, which connote femininity, as well as the female journalists operating under the guise of Konde.co. Through their work, these female writers strive to challenge gender inequalities by addressing the issue of domestic violence.